PENERAPAN METODE SAS DENGAN MENGGUNAKAN MEDIA PEMBELAJARAN FLASH CARD UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN PESERTA DIDIK SDN 1 TINIGI: Penelitian Tindakan Kelas (PTK) - Wulandari, Ayu; Hamna, Mustakim (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The success of the learning process is largely determined by the learning atmosphere created by the teacher. The absence of concrete learning media in instruction can influence students' low reading ability. The research goal was to determine the implementation of the SAS method using flash card media to improve the beginning reading ability of second-grade students at SDN 1 Tinigi. This research is a type of Classroom Action Research (CAR). The research action was carried out in two cycles. Data collection techniques included tests, observation, and documentation. The research results show that the initial data on students' beginning reading ability based on the Cycle I test was that 52% of students reached the Minimum Completion Criteria (KKM), and there was a further increase in the Cycle II test implementation, showing that 96% of students reached the KKM. This serves as proof that the Implementation of the SAS Method Using Flash Card Learning Media can improve Students' Beginning Reading Ability